Level of knowledge regarding healthcare document regulations among postgraduate stomatology students - Bernuy Torres, Luis Alexis (2025)
Objective: The objective of this study was to evaluate the level of knowledge regarding the management of standards in care documents, as established by the Peruvian Ministry of Health, among postgraduate dentistry students at a private university. Material and Methods: A descriptive and cross-sectional study was conducted with 153 postgraduate stomatology students from a private university. A virtual multiple-choice questionnaire with 30 questions was used, validated by experts (Content Validity Index: 0.86) and with a reliability of 0.82 (Cronbach's Alpha). Data collection was done using Google Forms, ensuring informed consent and confidentiality. Data were analyzed using descriptive statistics and tests such as Kolmogorov-Smirnov, Student's T-test, and ANOVA, with a significance level of 0.05. Results: The overall knowledge level regarding norms for healthcare documents was low, with an average score of 11.35 out of 30. Women and the 41-to-45-year age group showed slightly higher scores, with this difference being statistically significant for sex (p=0.037). Students with 16 to 20 years of professional experience and those specializing in Restorative Dentistry achieved the highest averages, though these differences were not statistically significant. Low averages were identified in specific areas such as odontograms, informed consent, and medication prescriptions. Conclusions: The study concludes that the knowledge level of postgraduate stomatology students regarding norms for healthcare documents is modest. A higher level of knowledge is observed in female participants and in the 41-to-45-year age group, as well as in those with 16 to 20 years of professional experience and in the Restorative Dentistry specialty. These findings